Systemic inflammation in xenograft recipients precedes activation of coagulation. (2015)
BACKGROUND: Dysregulation of coagulation is considered a major barrier against successful pig organ xenotransplantation in non-human primates. Inflammation is known to promote activation of coagulation. The role of pro-inflammatory factors as well as the relationship between inflammation and activation of coagulation in xenograft recipients is poorly understood.